Fiber-reinforced polymer plates for strengthening web opening in steel I-beams under cyclic loading. Issue 2 (January 2020) - Mustafa, Suzan AA; Fathy, Ebtsam; Rizk, Mostafa S
This article is interested in finding the most appropriate strengthening scheme for web opening in steel I-beam under cyclic loading. Different opening shapes and locations were strengthened using two different fiber-reinforced polymer plates: carbon fiber–reinforced polymer and basalt fiber–reinforced polymer. A three-dimensional nonlinear finite element model was adopted using ANSYS program. The results showed that the high strength of carbon fiber–reinforced polymer plates helped the steel beam to recover its original strength; however, noticeable reduction was observed in beam ductility and in the number of inelastic excursions that took place before failure. Moreover, remarkable difference in stress concentration existed at the position of the carbon fiber–reinforced polymer plate edges. Under cyclic loading, fiber-reinforced polymer composites with low modulus of elasticity such as basalt fiber–reinforced polymer managed to eliminate these deficiencies using longer strengthening length. The most appropriate strengthening length and scheme for each opening case were outlined.